Patrimonio ebraico e identità: Alcune note di geografia culturale (Altre Modernità, 2013)
Jewish Heritage is currently the focus of many studies, adopting different perspectives and theoretical approaches. Its true nature needs to be investigated also through the conceptual framework of Cultural Geography, dealing with enlightened identity processes that give rise to the multiple meaning of “Jewish Cultural Heritage”. Indeed, open or closed settlements and their vestiges, cultural and intercultural regional networks, production and distribution of ancient manuscripts, circulation of people, goods and ideas are all manifestations of the same social processes through different territories and over time.  Cultural Geography can offer an insight to more completely understand the relationships between material and immaterial, visible and invisible goods and values.The material and cultural history of Jewish communities, which has been and continues to be a rewarding field of interdisciplinary studies, is a worthwhile subject from which observations of Cultural Geography has been carried out and is offered in this writing.